Meaningful Work in Digital Labour: A Qualitative Case Study of Live Streaming Hosts in Indonesia - Nava Nurlita; Chandra Arifianto (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2026)
The rapid development of the digital workforce in e-commerce has transformed the characteristics of work, including the role of live streaming hosts. However, empirical studies on how these workers interpret their work are still limited, particularly in the context of MSMEs in Indonesia. This study aims to explore how live streaming hosts interpret their work, how this work shapes personal meaning, and how this work generates social contributions using the Work and Meaning Inventory (WAMI). This study uses a qualitative approach with a case study design at Babayaga Online Store in Tangerang City. Data were obtained through in-depth interviews with three hosts and one business owner, supported by observation and documentation, and then analyzed thematically. The results show that the hosts interpret their work not only as a source of income, but also as a means of self-development, increasing self-confidence, and a space for self-expression. The three dimensions of work meaningfulness identified include positive meaning from interactions with audiences, meaning formation through developing communication skills and empathy, and motivation to benefit consumers and business aspirations. This study extends the application of WAMI to the context of the digital workforce in Indonesian MSMEs and emphasizes the importance of a work environment that supports the personal growth of digital workers.